Effect of photoperiod on development and reproduction in Tasmanian lacewing Micromus tasmaniae (Walker) (Neuroptera Hemerobiidae) - Yadav, A.; He, X.Z.; Wang, Q. (New Zealand Plant Protection, 2008)
Tasmanian lacewing Micromus tasmaniae (Walker) is an important predator of many aphid species This study investigated the effect of four photoperiods on predation development and oviposition of M tasmaniae in the laboratory at 21 1C and 60 RH Results indicated that no individuals entered diapause at either immature or adult stage At each photoperiod late instar larvae consumed significantly more aphids than early instar larvae (P